Current understanding in conversion and application of tea waste biomass: A review. (October 2021) - Guo, Shasha; Kumar Awasthi, Mukesh; Wang, Yuefei; Xu, Ping
Graphical abstract: Highlights: Thermo-chemical and biological technologies for tea waste biomass conversion are reviewed. Tea waste derived biochar is an ideal bio-adsorbent on pollutants adsorption. Composting can enhance the nutrients of the bio-fertilizer derived from tea waste. Abstract: Along with the increasing consumption of tea and its extracts, the amount of tea waste grows rapidly, which not only results in huge biomass loss, but also increases environmental stress. In past years, interest has been attracted on utilization of tea waste biomass, and a lot of work has been carried out. This review summarized the progress in conversion of tea waste by thermo-chemical and biological technologies and analyzed the property of the derived products and their performance in applications. It was found that biochar derived from tea waste had relatively large surface area, porous structures, and abundant functional groups, and could be used as bio-adsorbents and catalysts and electrochemical energy storage, while the cost of its largescale production should be evaluated. Profoundly, biological conversion, including ensiling and composting, was suggested to be an effective way to develop the tea waste biomass in practice due to its low-cost and specific functions.